Zero-Offset VSP Monitoring of CO2 Storage: Impedance Inversion and Wedge Modelling at the Ketzin Pilot Site - Julia Götz; Stefan Lüth; Charlotte M. Krawczyk; Calin Cosma (International Journal of Geophysics)
At the CO2 storage pilot site near the town of Ketzin (35 km west of Berlin, Germany) the sandstone reservoir at 630 m–650 m depth is thin and heterogeneous. The time-lapse analysis of zero-offset VSP measurements shows that CO2-induced amplitude changes can be observed on near-well corridor stacks. Further, we investigate whether CO2-induced amplitude changes in the monitoring data can be used to derive geometrical and petrophysical parameters governing the migration of CO2 within a brine saturated sandstone aquifer. 2D seismic-elastic modelling is done to test the processing workflow and to perform a wedge modelling study for estimation of the vertical expansion of the CO2 plume. When using the NRMS error as a measure for the similarity between the modelled and recorded repeat traces, the best match is achieved for a plume thickness of 6-7 m within the reservoir sandstone of 8 m thickness. With band limited impedance inversion a velocity reduction at the top of the reservoir of 30%, influenced by casing reverberations as well as CO2 injection, is found. The relation of seismic amplitude to CO2 saturated layer thickness and CO2-induced changes in P-wave velocities are important parameters for the quantification of the injected CO2 volume.